Analysis of the Relationship Between Consumer-Based Brand Equity, Experiential Marketing, Customer Satisfaction, and Customer Loyalty at Starbucks Coffee in Karawang - Suhono; Ratih Hurriyati; Mokh Adieb Sultan (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2020)
This study aims to analyze the relationship between consumer-based brand equity, experiential marketing, customer satisfaction, and customer loyalty at Starbucks Coffee in Karawang. One of the marketing approaches to support the creation of customer loyalty is to market products using experiential marketing. By integrating the elements of emotion, logic, and general thought processes, a relationship with customers can be built which can not only increase customer satisfaction but also foster customer loyalty. The number of samples studied was 110 respondents via the internet, customers who had visited Starbucks Coffee in Karawang using non-probability sampling. The analytical tool used descriptive analysis and multiple regression methods. The results showed that the dimensions of consumer-based brand equity, namely physical quality, ideal self-congruence, and lifestyle congruence are factors that have a positive effect on customer satisfaction. However, staff behavior does not affect customer satisfaction. The experiential marketing dimension consisting of feelings, thoughts, and actions also has a positive relationship with customer satisfaction, although feelings do not affect customer satisfaction. In the evaluation of customer satisfaction, it is proven that customer satisfaction has a significant effect. This shows that the higher the customer satisfaction, the higher the loyalty of the Starbucks Coffee Karawang outlet customers